Upaya Guru Pendidikan Agama Islam Meningkatkan Konsentrasi Belajar Peserta Didik di Kelas IV SDN 15 Ampang Gadang - Jelita Oktafiani; Rita Febrianta; Khairuddin Khairuddin; Januar Januar (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
Efforts by Islamic Religious Education Teachers to Increase Learning Concentration for Class IV Students at SD Negeri 15 Ampang Gadang; This research discusses the strategies of Islamic religious teachers in increasing the level of student learning concentration in class IV of SD Negeri 15 Ampang Gadang. This research aims to describe the efforts made by Islamic teachers to increase the learning concentration of class IV students. The research method used is descriptive with a qualitative approach. Data collection was carried out through structured interviews, observation and documentation. The results of this research show that the efforts of Islamic religious teachers include cleaning and preparing students before entering class, getting used to praying and reading short surahs before starting learning, using interesting learning media to foster interest in learning, implementing interactive and fun teaching methods, and creating a learning environment. which is conducive.